Penggunaan Diksi pada Puisi Anak dalam Surat Kabar Kompas Edisi November 2015 dan Pemanfaatannya sebagai Bahan Pembelajaran Bahasa Indonesia SMP Kelas VIII - Selviana, Nessa; , Prof. Dr.H Abdul Ngalim, M, Hum (2016)
The purpose of this study is twofold. 1) Explain how the use of diction in nursery rhymes in the November issue of the newspaper Kompas, 2015. 2) To implement the method of use of diction in nursery rhymes are used as ingredients Indonesian pembalajaran in junior class VIII. The research is a qualitative study using descriptive methods. The data source is yaitupuisi children in research in the November issue of the newspaper Kompas, 2015. Data were analyzed in the form of words that included the use of diction. Data collection techniques in this study was conducted using see and note. Analysis of the data used in this study using agih. The results of this study, there are four forms of the use of words (diction). Four forms of use include the use of the word diction of the concrete and the abstract, the general use of the word-specialized, idiomatic use of the word, and the use of said bluntly. Researchers found 63 data on the use of words (diction) contained in children's poetry in the newspaper Kompas November 2015. The data includes 19 concrete words, abstract words 13, 10 common words, 12 words specifically, 6 idiomatic word, and one word straightforward, Words used in children's poetry in the newspaper there is a wide variety of uses diction. Syntactic study related to the use of diction can be used as teaching materials in the junior class VIII.